2018
DOI: 10.2147/ppa.s170984
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue of systemic lupus erythematosus in China: contributors and effects on the quality of life

Abstract: ObjectiveFatigue is a very common symptom of systemic lupus erythematosus (SLE), which significantly impairs patients’ quality of life. The purpose of this study is to evaluate contributors of fatigue and effects of fatigue on the quality of life in Chinese SLE patients.MethodsA survey of 119 SLE patients using the Fatigue Severity Scale (FSS) to assess the severity of fatigue was carried out. SLE patients completed the Systemic Lupus Erythematosus Disease Activity Index, the Hospital Anxiety and Depression Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
1
18
0
1
Order By: Relevance
“…using the FSS found significant correlation between fatigue and disease duration, too. 35 In addition, we found correlation between this tool and some domains of HRQoL like physical and emotional health; Cleanthous et al. reported negative associations with both dimensions (physical and mental component scores) of HRQoL.…”
Section: Discussionsupporting
confidence: 52%
“…using the FSS found significant correlation between fatigue and disease duration, too. 35 In addition, we found correlation between this tool and some domains of HRQoL like physical and emotional health; Cleanthous et al. reported negative associations with both dimensions (physical and mental component scores) of HRQoL.…”
Section: Discussionsupporting
confidence: 52%
“…A great body of evidence had reported that RA causes deterioration of all domains of QOL. Goma et al reported that all domains of SF36 were impaired in their 50 RA patients [43]. Moreover 464 RA patients were investigated by Katchamart and his colleagues for the quality of life using Thai version of EQ global health visual analogue scale (EQ VAS) and EuroQol five dimensional questionnaire (EQ5D).…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the arthritic effects can be observed in more than 95% of the affected individuals 6 . However, fatigue and tiredness are also frequent complaints when SLE is active 2,[7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…People affected by SLE experience many changes in daily life, including, in addition to physical and psychological symptoms, decreased muscle strength, changes in rhythm and productivity at work, limitations related to treatment and changes in body self-image and self-esteem 4,7,9 . In this sense, for many patients, the disease challenges the future and the meaning of life 10 .…”
Section: Introductionmentioning
confidence: 99%